Hot and cold - Ramsay, Helena; Bull, Peter; Farmer, Andrew (New York : Children's Press, 1998)
Text, activities, and simple experiments explain the scientific concepts of hot and cold with examples from everyday life.
Includes index.
L.A. Recommended Foreign Language.
4.8.
4.8
3-6
Keywords: Cold -- Juvenile literature; Heat -- Juvenile literature; Cold; Cold -- Experiments; Experiments; Heat; Heat -- Experiments; Cold; Cold -- Experiments; Experiments; Heat; Heat -- Experiments